Pulmonary artery denervation for treatment of a patient with pulmonary hypertension secondary to left heart disease - Zhang, Hang (Pulm Circ, 2016)
Abstract. Pulmonary hypertension (PH) predicts poor outcome in patients with left heart disease. A 62-year-old man was referred for heart failure associated with ischemic cardiomyopathy. He received a diagnosis of combined postcapillary and precapillary PH secondary to left heart disease on the basis of hemodynamic parameters. After the pulmonary artery denervation procedure was performed, hemodynamic parameters were markedly improved, which resulted in a significant increase in functional capacity.